Peranan Perkebunan Kelapa Sawit Rakyat dalam Mencapai Tujuan Ekonomi Sustainable Development Goals (SDGs) di Indonesia - Barus, Amelta Br; Ernah, Ernah (Universitas Galuh, 2024)
Smallholder oil palm plantations have a high contribution to economic growth. In addition, smallholder oil palm plantations also play an important role in achieving Indonesia’s SDGs economic goals. Sustainable Development Goals (SDGs) are a global platform with 17 main development goals and 169 target indicators. One of the main goals of SDGs is poverty alleviation. However, the problem of poverty in Indonesia is still relatively high. Based on data compiled by BPS, the number of poor people in Indonesia tends to fluctuate from 2013 to 2022. The concept of SDGs in poverty alleviation is in accordance with smallholder oil palm plantations, which have large market and employment opportunities. This study aims to determine the role of smallholder oil palm plantations in achieving Indonesia’s SDGs economic goals and factors affecting the poverty rate using quarterly data from 2013 to 2022. The research design uses qualitative descriptive approach with process documentation method using color mapping and Eviews12 software. The results show that the role of smallholder oil palm plantations in achieving Indonesia’s SDGs economic goals is categorized “Very Contributing” with an average score of 2,45. Factors that have a negative effect on poverty rate are palm oil production and labor. The price has a positive effect on poverty rate. While, the GDP of farms has no effect on the poverty rate. This is due to the inequality in economic growth patterns in Indonesia and the GDP advantage is not perceived equally by all people.